BRAND QUALITY IMPROVEMENT OF COMPOST PRODUCTS ORGANIC HOUSEHOLD WASTE TPS 3R SEKAR TANJUNG, WINDUSARI, MAGELANG - Adhi Surya Perdana; Indah Riadi Putri; Nurul Inayah; Solikhin Solikhin (Pasundan International of Community Services Journal (PICS-J), 2022)
Organic household waste is a problem for landfills that can cause unpleasant odors if not managed properly, the existence of TPS 3R Sekar Tanjung Windusari Magelang provides a solution to the problem through compost production. The benefits obtained include the organic waste that does not cause odor and is useful for plant media materials in addition to nutrients for plant nutritional needs. The production of TPS 3R Sekar Tanjung compost still produces bulk compost which is traded to farmers and consumers who love ornamental plants. Community service activities seek to improve the quality of compost product brands through label design, attractive packaging, and testing for C-Organic nutrient content, C/N ratio, pH, total N, P2O, and K2O at the Yogyakarta Agricultural Technology Research Center Laboratory in order to increase the economic value of compost products in the agricultural market.